2014
DOI: 10.1016/j.neuroscience.2014.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal pathways for hypertonic saline- and light-evoked corneal reflexes

Abstract: Cornea-evoked eyeblinks maintain tear film integrity on the ocular surface in response to dryness and protect the eye from real or potential damage. Eyelid movement following electrical stimulation has been well studied in humans and animals; however, the central neural pathways that mediate protective eyeblinks following natural nociceptive signals are less certain. The aim of this study was to assess the role of the trigeminal subnucleus interpolaris/caudalis (Vi/Vc) transition and subnucleus caudalis/upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…This suggested that the reduced spontaneous tear volume in our DE model (~50% reduction) was sufficient to excite ongoing activity of moisture-sensitive corneal afferent fibers that would be expected to increase during ocular surface dryness (Meng and Kurose 2013). These data support previous studies indicating that ocular stimulus intensity coding is a more pronounced feature of Vc/C1 neurons compared to Vi/Vc transition neurons (see Bereiter et al 2000), whereas the Vi/Vc transition may be more involved in homeostatic reflex responses such as lacrimation and eyeblink (Hirata et al 2004; Rahman et al 2014) and maintenance of a stable tear film.…”
Section: Discussionsupporting
confidence: 91%
“…This suggested that the reduced spontaneous tear volume in our DE model (~50% reduction) was sufficient to excite ongoing activity of moisture-sensitive corneal afferent fibers that would be expected to increase during ocular surface dryness (Meng and Kurose 2013). These data support previous studies indicating that ocular stimulus intensity coding is a more pronounced feature of Vc/C1 neurons compared to Vi/Vc transition neurons (see Bereiter et al 2000), whereas the Vi/Vc transition may be more involved in homeostatic reflex responses such as lacrimation and eyeblink (Hirata et al 2004; Rahman et al 2014) and maintenance of a stable tear film.…”
Section: Discussionsupporting
confidence: 91%
“…41 Second order neurons in this region of the TNc (trigeminal subnucleus caudalis/upper cervical cord junction) also showed increased Fos upon activation by bright light in rats 33 and are required for light-induced blink reflexes. 36 The pattern of light-evoked Fos 33 overlaps with the vibrissal dermatome in the rat TNc 48 and the area of Fos expression in our previous study. 41 …”
Section: Introductionmentioning
confidence: 58%
“…26,27 However, our studies demonstrate that squinting is also associated with activation of osmolarity sensing channels in the cornea of the rat. Rahman et al 28 show that hypertonic saline applied to the ocular surface of the rat elicits orbicularis muscle activity, which is dose dependent and is eliminated by corneal anesthesia, as well as by the blockade of trigeminal ganglion neurons. Recently, in the mouse, activation of TRPM8 channels in the cornea by increasing osmolarity was associated with an increased rate of blinking.…”
Section: Discussionmentioning
confidence: 99%